1982
DOI: 10.1093/ije/11.4.406
|View full text |Cite
|
Sign up to set email alerts
|

The Significance of Anti-HAV in Different Population Sectors in Lebanon: A Comparative Seroepidemiologic Study

Abstract: A comparative seroepidemiologic survey was performed on the prevalence of antibody to HAV (anti-HAV) in 772 subjects in Lebanon. The results show that 97.7% of the adult Lebanese carry anti-HAV in their sera irrespective of geographic or socioeconomic factors, as compared to 38.8% of the adult foreign population. In the paediatric group, the highest prevalence of anti-HAV was encountered at the age of 1-120 days indicating placental transfer of maternal anti-HAV. In the 1-5 year age group there is a sharp drop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…There is an evident shift in the epidemiology of HAV among the Lebanese population in comparison to data published in the early 1980s 20 . Others have shown this change and attributed it to improvement in hygiene and alteration in demographic factors, and concluded that Lebanon is entering a transitional phase between high and intermediate endemicity 21,22 …”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…There is an evident shift in the epidemiology of HAV among the Lebanese population in comparison to data published in the early 1980s 20 . Others have shown this change and attributed it to improvement in hygiene and alteration in demographic factors, and concluded that Lebanon is entering a transitional phase between high and intermediate endemicity 21,22 …”
Section: Discussionmentioning
confidence: 95%
“…Lebanon and the Middle East are considered to be areas of high endemicity for HAV infection. In 1982, 97.7% of Lebanese adults had anti‐HAV antibodies, irrespective of district and socioeconomic status 22 . In 2000, the overall prevalence of anti‐HAV antibodies among 740 children 6 months−15 years of age had decreased, but was still high in Northern Lebanon 25…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The HAV prevalence pattern as observed in this multicenter study was of intermediate endemicity and was representative of the population in governorates that constitute about 80% of the Lebanese population. The seroprevalence of hepatitis A in Lebanon was last documented in 1982, 11 although data on children aged 6 months to 15 years was updated in a study conducted in North Lebanon during 1996-1998. 12 HAV seroprevalence rate in 1982 was 97.7% and 40% in Lebanese adults and children aged 1-5 years, respectively, as compared with 78.1% and 10.5%, respectively, in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, published studies on HAV in Lebanon have been scarce, with fewer studies exploring the disease in children and adolescents [ Table 1 ]. [ 12 ],[ 13 ],[ 14 ],[ 15 ],[ 18 ]…”
Section: Resultsmentioning
confidence: 99%